2016
DOI: 10.1111/jce.12911
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Resynchronization Therapy Relieves Intractable Angina Due to Exercise‐Induced Left Bundle Branch Block Without Left Ventricular Systolic Dysfunction: A Detailed Case Study

Abstract: Exercise-induced left bundle branch block is rare and can be demonstrated with exercise testing. When the heart rate reaches a certain threshold, the QRS widens into left bundle branch block. This paper describes a patient with exercise-induced left bundle branch block related angina and dyspnea, who responded to cardiac resynchronization therapy. We documented the potential benefits of cardiac resynchronization therapy with a left ventricular rapid pacing study prior to its implantation. Although exercise-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…No defined treatment protocols are available for patients with painful LBBB syndrome, 19 but some studies have reported benefits with exercise training, cardiac resynchronization therapy by way of biventricular pacing, nonselective β-blocker therapy, and long-acting nitrates 5, 9, 10, 20, 21. More recently, Suryanarayana et al 22 reported His-bundle pacing as an effective management for painful LBBB syndrome in a patient with coexisting coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…No defined treatment protocols are available for patients with painful LBBB syndrome, 19 but some studies have reported benefits with exercise training, cardiac resynchronization therapy by way of biventricular pacing, nonselective β-blocker therapy, and long-acting nitrates 5, 9, 10, 20, 21. More recently, Suryanarayana et al 22 reported His-bundle pacing as an effective management for painful LBBB syndrome in a patient with coexisting coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that His-bundle pacing can control symptoms makes intuitive sense, since this strategy strives to approximate normal ventricular depolarization. It also suggests that CRT could offer similar benefit; indeed, a single case of successful treatment of painful LBBB with CRT has been reported 7 …”
Section: Discussionmentioning
confidence: 93%
“…An alternate approach is using device-based therapies for pacing with different modalities such as BiV pacing and His pacing, both of which would improve ventricular synchrony and lead to a narrow QRS complex. 5 , 6 Most recently, RV pacing was also found to be therapeutic in patients described by Shvilkin and colleagues 4 and Sroubek and colleagues. 7 The success of RV pacing in treating painful LBBB is truly perplexing, as it in itself leads to a wide QRS complex with a left bundle morphology.…”
Section: Discussionmentioning
confidence: 99%